2022
DOI: 10.3389/fmed.2022.954033
|View full text |Cite
|
Sign up to set email alerts
|

Is ectopic Cushing’s syndrome underdiagnosed in patients with small cell lung cancer?

Abstract: IntroductionEctopic Cushing’s syndrome (ECS) is an uncommon disorder. Recently, however, a larger proportion of patients with endogenous Cushing’s syndrome (CS) had ECS than has previously been reported.ObjectiveThe aim of this study was to determine whether ECS is an underdiagnosed disorder in patients with small-cell lung cancer (SCLC).Materials and methodsMedical records from consecutive patients diagnosed with SCLC at our hospital between 2013 and 2019 were reviewed (N = 213; mean age 69.5 ± 9 years; range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Throughout the entire selection process, 61 articles were retrieved, comprising 44 case reports ( 22 65 ), 7 case series ( 66 72 ), 9 retrospective studies ( 6 11 , 73 75 ), and 1 prospective study ( 76 ) published between 1985 and 2022 in English, Japanese, French, German, Spanish, and Korean. A total of 157 SCLC with PCS patients were involved in these 61 articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the entire selection process, 61 articles were retrieved, comprising 44 case reports ( 22 65 ), 7 case series ( 66 72 ), 9 retrospective studies ( 6 11 , 73 75 ), and 1 prospective study ( 76 ) published between 1985 and 2022 in English, Japanese, French, German, Spanish, and Korean. A total of 157 SCLC with PCS patients were involved in these 61 articles.…”
Section: Resultsmentioning
confidence: 99%
“…For differential diagnosis of CS, 132 SCLC patients (84.1% of all 157 patients) in 58 reports (95.1% of all 61 reports) were diagnosed with ECS. In 9 (15.5%) reports, 40 (30.3%) patients were diagnosed without strict evidence from combining imaging examinations with laboratory tests or reported with no mention of specific procedures for the diagnosis of ectopic hormone secretion ( 8 , 10 , 22 , 40 , 45 , 49 , 57 , 58 , 72 ). The patient reported by Cabral et al.…”
Section: Resultsmentioning
confidence: 99%
“…Small cell lung cancer has been reported to exhibit endocrine abnormalities. A study of 213 cases of small cell lung cancer found that the condition in one case was complicated and that in two cases was likely complicated with Cushing's syndrome associated with ectopic adrenocorticotropic hormone (ACTH) production (Piasecka et al 2022 ). Hypothyroidism and menstrual dysfunction associated with ectopic ACTH-producing tumors are reported to improve after drug treatment (Lin et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Small cell lung cancer has been reported to exhibit endocrine abnormalities. It was reported that in 213 cases of small cell lung cancer, one case was complicated and two cases were likely complicated with Cushing's syndrome associated with ectopic adrenocorticotropic hormone (ACTH)-stimulating hormone [14]. It has also been reported that hypothyroidism and menstrual dysfunction associated with ectopic ACTH-producing tumors improved after drug treatment [15].…”
Section: Discussionmentioning
confidence: 99%